Заславский vs Аткинсон: Из истории холодной войны [Zaslavsky _vs_ Atkinson: From the History of the Cold War] - Lapina, Galina (Slavica Revalensia, 2023)
The article discusses the confrontation of two reporters—Brooks Atkinson, a Moscow correspondent of The New York Times, and David Zaslavsky of Pravda in 1946. Having spent 10 months in Moscow, Brooks Atkinson perceived the signs of rising xenophobia and anti-Western sentiment in the USSR and wrote a series of articles truthfully portraying the situation behind the Iron Curtain. In response to his assertion that the Soviet people were denied freedom of speech and freedom of the press, Zaslavsky lashed out at the American reporter, blaming not only him, but Western journalism as such of being politically motivated. The vicious attack against the American journalist marked the beginning of the anti-Western campaign initiated by Soviet propaganda in the early period of the Cold War.